2016
DOI: 10.2135/cropsci2015.12.0747
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sugarcane Yield Potential across Large Numbers of Genotypes using Canopy Reflectance Measurements

Abstract: Canopy reflectance indices have been used to monitor plant growth and estimate yields in many field crops. Little is known if canopy reflectance of sugarcane (a complex hybrid of Saccharum spp.) can be used to estimate growth and yield potential across large numbers of genotypes (clones) in the early stages of a breeding program. The objectives of this study were to identify clonal variation in sugarcane canopy reflectance and yield components and to determine if there were any putative relationships between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
3
6
0
Order By: Relevance
“…Comparing NDVI, GNDVI, NDRE, and WDRVI, they all presented similar accuracy results for estimating the sugarcane yield. These results, except for NDRE, corroborate the results in Zhao et al [57] that reported no significant difference among the use of GNDVI, NDVI, and WDRVI for predicting sugarcane crop growth and yield. However, their approach based on linear regression models was different from the one in this study that tested both linear and non-linear models, as it was noted that the non-linear (RF regression) model performed better (higher R 2 , lower RMSE, and MAE), independent of the type of predictor variables.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Comparing NDVI, GNDVI, NDRE, and WDRVI, they all presented similar accuracy results for estimating the sugarcane yield. These results, except for NDRE, corroborate the results in Zhao et al [57] that reported no significant difference among the use of GNDVI, NDVI, and WDRVI for predicting sugarcane crop growth and yield. However, their approach based on linear regression models was different from the one in this study that tested both linear and non-linear models, as it was noted that the non-linear (RF regression) model performed better (higher R 2 , lower RMSE, and MAE), independent of the type of predictor variables.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, they proceeded using the simple linear regression and found R 2 values ranging from 0.22 to 0.41. Comparing their result with this study, the MLR presented lower R 2 than those found in Zhao et al [57], even using a greater number of predictor variables (22 instead of 8). Despite the higher R 2 found in the MLR model, the RF regression is the model that outperformed the linear approach, highlighting its suitability to be used to support yield prediction models based on orbital images.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The authors of [41] used the NDVI, among other indices, to demonstrate the influence of water deficit in the low fruit production in apple trees. The work in [42] measures sugarcane yield potential across a large number of genotypes using canopy reflectance measurements, such as NDVI. Recently, Johansen et al [43] investigated the use of high-spatial resolution satellite image data and geographic object-based image analysis, based on NDVI, to map putative sugarcane grub damage.…”
Section: Calculating the Vegetation Indexmentioning
confidence: 99%
“…Rebetzke et al [12] considered early-stage plant vigour via larger specific leaf area as an indirect selection target in wheat, and more recently, Kipp et al [13] and Duan et al [14] reported a high-throughput scoring method for early vigour using visual images that may improve wheat selections at early growth stage. Further, a strong correlation of sugarcane stalk population and yield with normalised difference vegetation index (NDVI) and reflectance at specific wavelengths was reported, suggesting that canopy reflectance measurements at the early growth stage can be used as a screening tool to estimate yield potential [15]. In maize, combining data from 62 wavebands and vegetation indices measured across multiple times using aerial phenotyping lead to an increase in prediction accuracy compared with using single-time-point data [16].…”
Section: Introductionmentioning
confidence: 99%